2015
DOI: 10.1186/s12888-015-0662-z
|View full text |Cite
|
Sign up to set email alerts
|

Type specific Real time PCR for detection of human herpes virus 6 in schizophrenia and bipolar patients: a case control study

Abstract: BackgroundSchizophrenia (SC) and bipolar disorder (BD) are among the most devastating diseases worldwide. There are several lines of evidence suggesting that viruses may play significant roles in the etiology of these mental disorders. The aim of this study was the detection of HHV-6A/B in the peripheral blood mononuclear cells (PBMC) of SC and BD patients versus the healthy control (HC) subjects using a new method of type-specific Real time PCR analysis.MethodsA type-specific Real time PCR was performed for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The only previous study of HHV-6A/B in brain in mood disorders, by Conejero-Goldberg et al (2003) , identified HHV-6B DNA in one BPD and one CON case in the orbital fontal cortex, using a consensus PCR assay with low sensitivity ( Conejero-Goldberg et al, 2003 ). Other studies using blood samples found an association of serum HHV-6A/B IgG with SCZ in military personnel ( Niebuhr et al, 2008 ), and no difference from controls for HHV-6A and HHV-6B DNA in peripheral blood mononuclear cells ( Yavarian et al, 2015 ). It is difficult to reconcile our findings with previous studies or to explain why we found HHV-6A and HHV-6B more frequently in MDD and BPD compared to SCZ.…”
Section: Discussionmentioning
confidence: 86%
“…The only previous study of HHV-6A/B in brain in mood disorders, by Conejero-Goldberg et al (2003) , identified HHV-6B DNA in one BPD and one CON case in the orbital fontal cortex, using a consensus PCR assay with low sensitivity ( Conejero-Goldberg et al, 2003 ). Other studies using blood samples found an association of serum HHV-6A/B IgG with SCZ in military personnel ( Niebuhr et al, 2008 ), and no difference from controls for HHV-6A and HHV-6B DNA in peripheral blood mononuclear cells ( Yavarian et al, 2015 ). It is difficult to reconcile our findings with previous studies or to explain why we found HHV-6A and HHV-6B more frequently in MDD and BPD compared to SCZ.…”
Section: Discussionmentioning
confidence: 86%
“…Real‐time Taqman PCR was undertaken using consensus primers detecting both HHV‐6A and HHV‐6B: Primers (HHV6U41‐F4: 5′‐CGGAACATTGTTGAGCAGAAA‐3′, HHV6U41‐R106: 5′‐ AAGAAGAATCCCTTGTCTGGC‐3′) and species‐specific probes (HHV‐6A U41‐ProbeA: FAM‐ CTCTAAGCACGAAATCTTCACATTCGGAAACA‐TAMRA, HHV‐6B U41‐ProbeB: JOE‐CTCTAAGCACGAAATTTTGACATTCGGAAACA‐BHQ1). The thermocycling conditions were as follows: Denaturation at 95°C for 3 minutes, followed by 45 cycles of denaturation at 95°C for 15 seconds, annealing at 55°C for 30 seconds and extension at 60°C for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Исполь зовали набор реагентов для проведения ПЦРРВ в при сутствии интеркалирующего красителя SYBR Green I (ООО «Синтол», Россия) и зондов TaqMan. Система для определения ДНК ВГЧ6 в клиническом материале была отработана ранее [9].…”
Section: материалы и методыunclassified